Early-stage sustainability assessment to assist with material selection: a case study for biobased printer panels. (1st November 2016) - Broeren, M.L.M.; Molenveld, K.; van den Oever, M.J.A.; Patel, M.K.; Worrell, E.; Shen, L.
Abstract: This paper aims to incorporate sustainability assessment into the material selection processes during early-stage product (re)design, when time and data availability for such assessments are usually limited. A material selection framework is presented and illustrated step-by-step with a case study aiming to identify biobased alternatives for petrochemical plastics used for (flame retardant) panels. After an initial screening step, the technical performance of selected materials is measured. A cradle-to-grave screening life cycle assessment compares the environmental performance of the candidate and reference materials on greenhouse gas emissions, non-renewable energy use and agricultural land use per kilogram. A simplified cost analysis is performed. The environmental and economic indicators are corrected for each candidate's technical performance by estimating expected weight changes in the final product based on material indices . In this case study, two biobased plastics are found to offer equal or improved environmental/economic performance compared to reference materials. Furthermore, the case study shows that additive production can significantly contribute to the plastics' environmental impacts, e.g. accounting for 5–40% of their cradle-to-grave greenhouse gas emissions. The case study demonstrated that the proposed materials selection framework is a useful tool for early-stage product design. Highlights: A framework to identify sustainable materials for product (re)design is introduced. Selection and evaluation based on technical, environmental and economic performance. The framework is tested in case study for biobased (flame retardant) panels. Two biobased materials found to offer lower/equivalent environmental impacts and cost. Additives account for up to 45% of panel GHG emissions in cradle-to-grave LCA.